The application of phytoremediation Lemna perpusilla to increase the production performance of Nile tilapia Oreochromis niloticus in a recirculation system - Utami, Rina Hesti; Nirmala, Kukuh; Rusmana, Iman; Djokosetiyanto, Daniel; Hastuti, Yuni Puji (Indonesian Society of Scientific Aquaculture (ISSA), 2018)
ABSTRACTThis study aimed to evaluate the production performance and physiological of Nile tilapia using Lemna perpusilla as a phytoremediator in a recirculation system. A completely randomized design with two treatments and three replications was applied. The treatments were Nile tilapia cultured with L. perpusilla (TL) and without L. perpusilla (L). The experimental fish in this study was the juvenile of Nile tilapia with a body length of 9.98 ± 0.08 cm and an average weight of 36.27 ± 1.07 g. The stocking density was 46 fish/pond and the container size was 275×100×60 cm3 and was separated in two areas using a fiber separator screen of 55.9% area for fish culture and 44.1% for L. perpusilla. The Nile tilapias were reared for 60 days, fed with commercial diet and fresh L. Perpusilla with amount 2% and 1% of biomass, respectively. They were fed three times a day with fresh L. perpusilla at noon and commercial diet in the morning and afternoon. The results showed that the Nile tilapia reared with L. perpusilla phytoremediation had normal physiological condition and production performance. The predominances of this system were lower feed conversion ratio value, more optimal values of feeding efficiency, and higher coefficient of weight uniformity. Keywords: Lemna perpusilla, physiological condition, phytoremediation, production performance. ABSTRAKPenelitian ini bertujuan mengevaluasi kinerja produksi dan fisiologi ikan nila dengan penggunaan Lemna perpusilla sebagai fitoremediator pada sistem resirkulasi. Rancangan penelitian yang digunakan adalah acak lengkap dengan dua perlakuan dan tiga ulangan. Ikan nila dipelihara pada kolam tanpa L. perpusilla (TL) dan ikan nila dipelihara pada kolam dengan L. perpusilla (L). Ikan yang digunakan dalam penelitian ini adalah benih ikan nila dengan panjang baku 9,98 ± 0,08 cm dan bobot rata-rata 36,27 ± 1,07 g. Padat tebar ikan tiap kolam pemeliharaan 46 ekor/kolamdengan ukuran kolam 275×100×60 cm3. Setiap kolam diberi sekat dengan luasan 44,1% L. perpusilla dari luasan kolam. Ikan nila dipelihara selama 60 hari pemeliharaan dengan pakan berupa pakan komersial dan L. perpusilla dengan jumlah pakan masing-masing 2% dan 1% dari biomassa. Pada pagi dan sore hari diberi pakan komersial, dan siang hari ikan diberi pakan L. perpusilla. Hasil penelitian ini menunjukkan bahwa ikan nila yang dipelihara dengan fitoremediasi L. perpusilla menghasilkan kinerja produksi dan kondisi fisiologis yang normal. Keunggulan sistem ini adalah menghasilkan nilai konversi pakan yang lebih rendah, nilai efisiensi pemberian pakan, dan koefisien keseragaman bobot yang lebih tinggi. Kata kunci : fitoremediasi, Lemna perpusilla, kondisi fisiologis, kinerja produksi.